Neural Evidence of Regret and Its Implications for Investor Behavior - Frydman, Cary; Camerer, Colin (Review of Financial Studies, 2016)
We use neural data collected from an experimental asset market to measure regret preferences while subjects trade stocks. When subjects observe a positive return for a stock they chose not to purchase, a regret signal is observed in an area of the brain that is commonly active during reward processing. Subjects are unwilling to repurchase stocks that have recently increased in price, even though this is suboptimal in our experiment. The strength of stock repurchasing mistakes is correlated with the neural measures of regret. Subjects with high rates of repurchasing mistakes also exhibit large disposition effects.